Incident HIV acquisition among pregnant women in Botswana: findings from the Tsepamo birth outcomes surveillance study - Aamirah Mussa; Gloria Katuta Mayondi; Modiegi Diseko; Judith Mabuta; Mompati Mmalane; Joseph Makhema; Shahin Lockman; Chelsea Morroni; Roger Shapiro; Rebecca Zash (Journal of the International AIDS Society, 2023)
Abstract Introduction In Botswana, where almost all pregnant women known to have HIV receive antiretroviral therapy, a large proportion of vertical HIV transmission may occur among women with incident undiagnosed HIV infection during pregnancy. Botswana guidelines recommend repeat HIV testing every 3 months in pregnancy, with at least one test in the third trimester. We evaluated the rate of repeat HIV testing, calculated HIV incidence during pregnancy and estimated missed seroconversions. Methods In the Botswana Tsepamo Study, we abstracted HIV test dates and results from obstetric records of all women who delivered at maternity wards in 18 communities between 7th May 2017 and 20th August 2021. We defined seroconversion as an initial negative/indeterminate HIV test in pregnancy followed by a positive test during pregnancy/at delivery. The incidence rate (IR) of seroconversion was calculated among women with > = 2 known test dates. Missed seroconversions were estimated among women without a test in the third trimester by applying the IR to the time after the last HIV test until delivery. Results Among 103,529 women delivering in the study period testing negative at the first test and with known conception and HIV test dates, 29,085 (28%) were tested in one trimester of pregnancy, 73,156 (71%) were tested in ≥ 2 trimesters of pregnancy and 9628 (9%) had a test in all trimesters. A total of 78,162 (75%) women had a third‐trimester test. There were 223 seroconversions (2.58/1000 pregnancies, 0.26%) among those with ≥ 2 known HIV test dates, yielding an IR of 0.69/100 person‐years. Among 25,289 women who did not have a test in the third trimester, we estimate approximately 58 seroconversions may have been missed during pregnancy due to a lack of repeat testing. Factors associated with seroconversion during pregnancy included younger age, less education and not being married. Conclusions More than two‐thirds of women had repeat HIV testing in pregnancy and HIV incidence was low. However, an estimated 21% of seroconversions in pregnancy were likely missed due to a lack of re‐testing. To reach the goal of zero new paediatric HIV infections, Botswana will need to intensify repeat HIV testing in the third trimester of pregnancy.